Natural Therapeutic Agents' Efficacy in Preventive Strategies against the Periodontal Pathogen Aggregatibacter actinomycetemcomitans: An In Vitro Study - Sima Hermes; Sham Alatwan; Anders Johansson; Anna Bogren (MDPI AG, 2024)
Adolescent carriers of the Aggregatibacter actinomycetemcomitans JP2 genotype have an increased risk of developing periodontitis, due to the bacterium's high leukotoxin (LtxA) production. LtxA contributes to marginal bone loss by killing immunity cells, thus activating the proinflammatory interleukin-1β (IL-1β), which, in turn, activates the osteoclasts. A possible strategy to prevent periodontitis might be to neutralize LtxA in JP2-infected individuals. The aim of this study was to investigate whether extracts from Matcha or Guava leaves can prolong the viability of macrophages in cell cultures by neutralizing the highly leukotoxic JP2 genotype bacteria. The A. actinomycetemcomitans JP2 genotype was pretreated with extracts from either Matcha or Guava leaves. Later, the extracts were rinsed off, before JP2 bacteria were exposed to macrophage cell cultures. The experiment was repeated, where JP2 bacteria were persistently treated with the extracts instead, i.e., the extracts were not rinsed off. The macrophage viability after bacterial exposure was analyzed and compared with that of macrophages exposed to untreated JP2 bacteria. IL-1β secretion in the cell culture medium was quantified in all group samples. Pretreatment of the A. actinomycetemcomitans JP2 genotype with Matcha or Guava leaf extracts moderately neutralized LtxA activity, which resulted in prolonged macrophage viability and decreased IL-1β secretion. These effects of prolonged macrophage viability were enhanced when extracts were persistently present during the exposure period. The results indicate that Matcha and Guava leaf extracts have effects on the virulence of the A. actinomycetemcomitans JP2 genotype that may be useful in future treatment strategies to prevent periodontitis in JP2 bacterium carriers.